Research priorities for nursing care of infacts, children and adolescents: a West Australian Delphi study - Wilson, Sally; Ramelet, A.; Zuiderduyn, S. (Blackwell Publishing, 2010)
This paper describes a study aimed to identify research priorities for the care of infants, children and adolescents at the sole tertiary referral hospital for children in Western Australia. The secondary aim was to stimulate nurses to explore clinical problems that would require further inquiry. Planning for research is an essential stage of research development: involving clinicians in this exercise is likely to foster research partnerships that are pertinent to clinical practice. Nursing research priorities for the paediatric population have not previously been reported in Australia. Thirty-seven research priorities were identified. The identification of research priorities by nurses provided research direction for the health service and potentially other similar health institutions for children and adolescents in Australia and internationally.